Estudo metanalítico do estresse por calor na lactação de matrizes suínas - Ribeiro, Bruna Pontara Vilas Boas (2016)
The aim of this study was to (1) evaluate the effect of high temperatures on lactating of performance and (2) to evaluate the effect of heat on variables related to litter, through a meta-analytic study. a database was built according to the methodology of systematic review. The database totaled 2,222 lactating females. The study period was 17 years (Jan. 2000 to February. 2016). The variables with the largest representation in the number of studies for the piglet weight at 21 days (kg) and litter weight at 21 days (kg) were 49.88 and 51.08% respectively of the minimum and maximum weight. The daily temperature (TºC) that characterized the thermal comfort or heat ranged from 15 to 32°C. The behavior of physiological variables, rectal temperature and respiratory rate were similar when comparing the thermal comfort and the heat stress, the values increase considerably, mainly for respiratory rate. The loss of thickness after fat - delivery (mm) showed a positive correlation with temperature, but not significant (P> 0.05). The nutrient consumption behavior follows an inverse correlation with increased temperature. The weight of piglets at 21 days (kg) in the thermal comfort is higher than 0,561kg compared to the heat stress. The live birth variables and piglet weight gain were significant at (P <0.05) with also high and negative correlation with temperature. The rectal temperature physiological variables (°C) and respiratory rate (mov.min) presented figures showing the variation between comfort environment and heat stress, being approximately 0.5 (ºC) and 37.05 (mov.min). The feed intake (kg/d) and milk production (kg/d) had high and negative correlations. The room temperature is directly related to the matrix performance variables and litter performance variables, demonstrating that the high temperature environment has a significant negative effect on feed intake and more generally on the productive and reproductive performance of matrices lactation.